Crossmatch Results After Repeated Transfusions - Horian, Erinca; Lismayanti, Leni; Sugianli, Adhi Kristianto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Patients with thalassemia, chronic kidney disease, hematologic and non-hematologic malignancies may require repeated transfusions. Repeated transfusions can have a detrimental effect, leading to the formation of alloantibodies and/or autoantibodies. These antibodies can cause incompatible crossmatch results. This study aims to identify the clinical characteristics of patients with incompatible crossmatch results after repeated transfusions, to ensure safe transfusions. This study is a cross-sectional, observational descriptive study conducted at Dr. Hasan Sadikin General Hospital from January to December 2022. Patients were included if they had received more than one transfusion within the past year, defined as 'repeated transfusions'. The following data were collected: age, gender, blood type, diagnosis, quantity of blood bags, total number of transfusions, interval between transfusions, history of incompatibility, and Coombs Test. The data were obtained through the laboratory information system and from blood request forms in the Blood Service Unit. Out of 2285 subjects receiving repeated transfusions, 38.1% experienced crossmatch incompatibility. The majority (91.2%) of these cases were minor. Crossmatch incompatibility occurred more frequently in subjects under the age of 15 (22.6-23.3%) and those with diagnosis of thalassemia (25.6-27.3%). Most subjects with minor crossmatch incompatibility had a history of receiving more than four blood bags (51.9-60%), an interval between transfusions of four weeks or less (92.2-92.8%), and a history of previous incompatibility (72.1-80.5%). The important clinical characteristics of patients with incompatible crossmatch results after repeated transfusions were age, underlying diagnosis, quantity of blood bags, interval between transfusions, and history of previous crossmatch incompatibility.